Power smoothing method of PMSG based grid integrated wind energy conversion system using BESS/DSTATCOM - N. S., Jayalakshmi; Gaonkar, D. N.; Jain, Sanchit Kumar (Institute of Advanced Engineering and Science, 2019)
The output of the PMSG based wind energy conversion system (WECS) is fluctuating in nature due to intermittency of wind speed. The distribution static synchronous compensator (DSTATCOM) incorporated with the battery energy storage system (BESS) is used to smooth the power produced from wind generator system. The control strategy of BESS/DSTATCOM and its integration to mitigate the power fluctuations of grid connected WECS is presented. Three-leg three-phase voltage source converter (VSC) based DSTATCOM is used and the battery current is controlled to smooth the net power injected to the utility grid from wind power generation system. The control strategy implemented has the capability of supplying the required amount of power to the utility with help of batteries. The PQ control strategy is employed to control the three-phase inverter for managing power exchange with the utility grid. The real time wind speed data is considered for the simulation study of the system. The effectiveness of the control strategy of the system is validated through the simulation results in MATLAB/Simulink environment.